2011
DOI: 10.1007/978-3-642-23771-3_2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Haptic Feedback in Exergames

Abstract: Abstract. Exergames combine entertainment and exercise in an effort to encourage people to be more physically active. Although exergames require active input, interactions are less physical than those experienced in real-world exercise. Interactions can feel artificial, limiting the captivating experience exergames aim to provide. To address this problem, haptics have been proposed as a means of providing additional feedback to players through the sense of touch. However, there is very little empirical evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
(33 reference statements)
1
10
0
Order By: Relevance
“…8 Well-implemented task-control movements could affect multiple aspects of videogame experience by increasing realism and interactivity. 64 Spontaneous task-facilitating movements may influence game play and experience by improving performance or perceptions of performance. These movements are not required by the game but may improve players' precision or timing (e.g., tapping one's foot to the beat).…”
Section: Body Movement In Videogames and Enjoymentmentioning
confidence: 99%
“…8 Well-implemented task-control movements could affect multiple aspects of videogame experience by increasing realism and interactivity. 64 Spontaneous task-facilitating movements may influence game play and experience by improving performance or perceptions of performance. These movements are not required by the game but may improve players' precision or timing (e.g., tapping one's foot to the beat).…”
Section: Body Movement In Videogames and Enjoymentmentioning
confidence: 99%
“…The games include the Balloon Burst, Truck Pull and Pedal Race exergames [35], the Eliminate 3-D first-person shooter, the Speed Demons racing game, the Growl Patrol ubiquitous game [23], and the Liberi persistent world building game [18]. The toolkit has also been used to implement the OrMiS tabletop military simulation tool [29].…”
Section: Experiencementioning
confidence: 99%
“…Pradana et al [4] used haptic feedback to enhance text messaging and add extra emotional context to messages. Stach and Graham [5] demonstrated that haptic feedback can be effective in games that promote an active lifestyle. These examples show that haptic feedback can be potentially integrated into many everyday actions, thus inspiring our work.…”
Section: Introductionmentioning
confidence: 98%